2012
DOI: 10.3389/fgene.2012.00287
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics of Cancer ncRNA in High Throughput Sequencing: Present State and Challenges

Abstract: The numerous genome sequencing projects produced unprecedented amount of data providing significant information to the discovery of novel non-coding RNA (ncRNA). Several ncRNAs have been described to control gene expression and display important role during cell differentiation and homeostasis. In the last decade, high throughput methods in conjunction with approaches in bioinformatics have been used to identify, classify, and evaluate the expression of hundreds of ncRNA in normal and pathological states, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 130 publications
0
7
0
Order By: Relevance
“…More specifically, complete analytical pipelines for noncoding RNAs (ncRNAs) are also needed, as aberrant patterns in (very) long and noncoding RNAs have been explored as important biomarkers for the classification of subtypes of cancers and other diseases, as primary factors in oncogenesis, and for therapeutic effects 69,71,72,76 .…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, complete analytical pipelines for noncoding RNAs (ncRNAs) are also needed, as aberrant patterns in (very) long and noncoding RNAs have been explored as important biomarkers for the classification of subtypes of cancers and other diseases, as primary factors in oncogenesis, and for therapeutic effects 69,71,72,76 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, RNA-Seq enabled the discovery of new potential splice isoforms [8,9] and the analysis of transcript expression levels [10] in different cell types and conditions. The methods of sequencing and the assembly of reads have been compared [11] and improved over the past few years, promoting new perspectives in transcriptomics [12], including noncoding RNAs (reviewed in [13]). …”
Section: Introductionmentioning
confidence: 99%
“…With the progress and development of biotechnology such as genome sequencing, it has been confirmed that more than 97% of the transcripts in the human genome do not have the function of coding protein, that is, non-coding RNA (ncRNA), which mainly includes small non-coding RNA (miRNA) and long non-coding RNA(lncRNA) [ 3 ]. MiRNAs generally have 18 to 25 nucleotides, and their sequences are highly conserved in evolution.…”
Section: Introductionmentioning
confidence: 99%